Pemanfaatan Analisa Swot Dalam Mewujudkan Wirausaha Berbasis BUMDes Di Desa Jambi Tulo Kecamatan Maro Sebo Kabupaten Muaro Jambi - Pratiwi Indah Sari; Mulia Inda Purwati (Universitas Batanghari Jambi, 2024)
This research aims to determine the effect of using SWOT analysis in realizing BUMDes-based entrepreneurship in Parit Panjang Hamlet, Jambi Tulo Village, Maro Sebo District, Muaro Jambi Regency. The type of research used is qualitative research with a case study approach with the scope of this research being BUMDes members in Parit Panjang Hamlet, Jambi Tulo Village, Maro Sebo District, Muaro Jambi Regency. The results of the research show that the SWOT analysis not only looks at four aspects from different points of view for the sustainability of BUMDes in Parit Panjang Hamlet, Jambi Tulo Village, Maro Sebo District, Muaro Jambi Regency, but is able to provide a way for the creation of job opportunities for the community to become entrepreneurs and founders of successful MSMEs. not there yet.